Method and device for testing magnetic substance of battery negative electrode material

By combining ultrasonic treatment with a polytetrafluoroethylene (PTFE) magnetic rod, the problem of incomplete adsorption of magnetic materials caused by the porosity of lithium battery anode materials has been solved, enabling more accurate magnetic material testing. This method is applicable to conventional laboratory equipment and improves the accuracy and reliability of the tests.

CN121207964APending Publication Date: 2025-12-26SHAANXI SHAANXI COAL DETECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511407993.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

In existing technologies, the magnetic material testing of lithium battery anode materials is difficult due to the large specific surface area and porosity of the materials, which makes it difficult for magnetic materials to be completely adsorbed by conventional magnetic rods. This leads to deviations in test results and affects industrial production and environmental safety.

Method used

An ultrasonic treatment combined with the adsorption of a PTFE-coated magnetic rod was used. The magnetic material was desorbed from the negative electrode material by ultrasound, and acid digestion was used to ensure complete adsorption and testing of the magnetic material. The results were then measured using an inductively coupled plasma instrument.

Benefits of technology

It improves the accuracy and reliability of magnetic material testing, reduces detection costs, is suitable for routine laboratory equipment, simplifies operating procedures, is applicable to pretreatment in inductively coupled plasma atomic emission spectrometry and mass spectrometry, and provides more accurate data guidance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121207964A_ABST
    Figure CN121207964A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a device for testing a magnetic substance of a battery negative electrode material, and the method comprises the following steps: dispersing the battery negative electrode material in absolute ethyl alcohol to form a mixed solution; performing ultrasonic pretreatment on the mixed solution to desorb the magnetic substance from the battery negative electrode material to form a mixed solution after ultrasonic treatment; adsorbing a magnetic substance desorbed from a battery negative electrode material through a magnetic rod coated with polytetrafluoroethylene; after the adsorption is finished, cleaning the magnetic bar which adsorbs the magnetic substance and is coated with polytetrafluoroethylene, and carrying out acid digestion treatment to obtain a digestion solution; based on the digestion solution, the content of the magnetic substance is tested through an inductively coupled plasma instrument, and testing of the magnetic substance of the battery negative electrode material is completed. The problem of incomplete adsorption caused by retention of magnetic substances in holes due to the porosity of the negative electrode material can be improved, so that the desorbed magnetic substances are captured immediately; the method can be compatible with conventional equipment in a laboratory, is economical and simple and convenient to operate, and improves the accuracy and reliability of the test to a greater extent.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of testing and analyzing battery negative electrode materials, and particularly relates to a testing method and device for magnetic substances of battery negative electrode materials. BACKGROUND

[0002] If the content of magnetic substances of battery negative electrode materials is too high, dendrites will penetrate the separator during charging and discharging, causing positive and negative electrode contact, battery short circuit, and further causing violent combustion or even explosion, affecting battery and automobile safety, and toxic and harmful substances in the battery will be released into the atmosphere, causing serious impact on the environment. Therefore, it is necessary to accurately test the magnetic substances in battery negative electrode materials. Currently, the testing of magnetic substances in positive electrode materials and negative electrode materials of lithium batteries mainly refers to two standards, GB / T33827-2017 "Determination method of magnetic substance content in nanometer negative electrode material for lithium battery" and GB / T24533-2019 "Graphite-based negative electrode material for lithium ion battery" Appendix K, which disperses the sample in an ethanol medium, adsorbs it by rolling with a magnetic rod, then digests the adsorbed material with an acid solution, and then measures the content of iron, cobalt, chromium, nickel and zinc by inductively coupled plasma optical emission spectrometer (ICP-OES) or inductively coupled plasma mass spectrometer (ICP-MS). However, it is found in the experiment that due to the difference between the testers and the testing devices, the accuracy and precision of the test results cannot be guaranteed, and there is a large degree of deviation between the test results and the true value. The main reason is that most of the graphite-based or silicon-based negative electrode materials are porous materials with large specific surface area, and part of the magnetic substances will inevitably be adsorbed in the pores of the material, which cannot be completely adsorbed by the magnetic rod during the adsorption process, resulting in deviation between the test value and the true value. In addition, there is no suitable laboratory pretreatment device for the testing process of battery material magnetic substances, which is the reason for the deviation in the testing process of battery material magnetic substances. In summary, due to the large specific surface area and porous material of the current negative electrode material for lithium battery, the magnetic substances are difficult to be completely adsorbed by the conventional magnetic rod during the adsorption process, resulting in a smaller value of the finally tested magnetic substances, which may cause incorrect guidance to industrial production and environmental evaluation, and affect the electrochemical performance and environmental safety of the subsequent battery. SUMMARY

[0003] The present application provides a testing method and device for magnetic substances of battery negative electrode materials, which aims to solve the problem that the current negative electrode material for lithium battery is difficult to be completely adsorbed by the conventional magnetic rod during the adsorption process of magnetic substances due to the large specific surface area and porous material of the material, resulting in a smaller value of the finally tested magnetic substances, which may cause incorrect guidance to industrial production and environmental evaluation, and affect the electrochemical performance and environmental safety of the subsequent battery.

[0004] To achieve the above object, the application adopts the following technical scheme: The application provides a method for testing magnetic substances in a battery negative electrode material, comprising the following steps: S1, dispersing the battery negative electrode material in anhydrous ethanol to form a mixed solution; S2, performing ultrasonic pretreatment on the mixed solution so as to detach the magnetic substances from the battery negative electrode material and form an ultrasonic-treated mixed solution; S3, adsorbing the detached magnetic substances from the battery negative electrode material by a magnetic bar coated with polytetrafluoroethylene in the ultrasonic-treated mixed solution; S4, after the adsorption is completed, cleaning the magnetic bar coated with polytetrafluoroethylene to which the magnetic substances are adsorbed, and obtaining a digestion solution after acid digestion treatment; S5, based on the digestion solution, testing the content of the magnetic substances by an inductively coupled plasma instrument to complete the testing of the magnetic substances in the battery negative electrode material.

[0005] In some embodiments, in S1, the mass ratio of the lithium battery negative electrode material to the anhydrous ethanol in the mixed solution is controlled to be 2:3-20.

[0006] In some embodiments, in S2, the parameters in the ultrasonic pretreatment are controlled as follows: The ultrasonic power is controlled to be 100W-500W, the ultrasonic time is controlled to be 0.3h-1h, and the mixed solution is paused and turned over at least three times during the ultrasonic treatment.

[0007] In some embodiments, in S3, the adsorption of the magnetic bar coated with polytetrafluoroethylene is realized in a rolling adsorption or stirring adsorption mode.

[0008] In some embodiments, in S3, the magnetic field strength of the magnetic bar coated with polytetrafluoroethylene is 6000GS-14000GS, and the time for ring adsorption of the magnetic bar coated with polytetrafluoroethylene is controlled to be 10min-60min.

[0009] In some embodiments, in S4, the operation of cleaning the magnetic bar coated with polytetrafluoroethylene to which the magnetic substances are adsorbed comprises: first cleaning with pure water to remove residual negative electrode material, and then cleaning with ethanol.

[0010] In some embodiments, in S4, the acid digestion treatment adopts aqua regia as a digestion reagent, and the magnetic bar coated with polytetrafluoroethylene to which the magnetic substances are adsorbed is placed in a container containing the aqua regia for acid digestion treatment; The amount of aqua regia is controlled as follows: the mass ratio of aqua regia to the negative electrode material is 3:25-3:100; and water is added as needed after adding aqua regia in the container until the liquid in the container submerges the magnetic rods coated with polytetrafluoroethylene that have adsorbed magnetic substances.

[0011] Further, in the acid digestion process in S4, the temperature of acid digestion is controlled to be 120-180 DEG C, and the time of acid digestion is controlled to be 20-40 min.

[0012] In some embodiments, in S5, the inductively coupled plasma instrument is an inductively coupled plasma optical emission spectrometer or an inductively coupled plasma mass spectrometer.

[0013] The application also provides a testing device for battery negative electrode material magnetic substances, which is used to execute the above-mentioned testing method for battery negative electrode material magnetic substances, and comprises an ultrasonic device water bath part and an ultrasonic device control base arranged from top to bottom.

[0014] Compared with the prior art, the application has the following beneficial effects: The application forms a complete testing process for battery negative electrode material magnetic substances by combining ultrasonic desorption with adsorption of the magnetic rods coated with polytetrafluoroethylene, and improves the problem of incomplete adsorption caused by retention of magnetic substances in the pores of the negative electrode material in the traditional method. The ultrasonic treatment loosens and desorbs the magnetic substances in the pores, and the strong ultrasonic waves are used to desorb and disperse the magnetic substances, thus fundamentally solving the problem of low adsorption rate. The mixed liquid is directly subjected to magnetic adsorption after ultrasonic treatment, so as to ensure instant capture of the desorbed magnetic substances and prevent re-adsorption. The testing is performed after acid digestion, so as to ensure data accuracy. The application can be compatible with conventional laboratory equipment, and only requires basic equipment such as an ultrasonic instrument, magnetic rods coated with polytetrafluoroethylene, and a heating device, thus significantly reducing detection cost and threshold. Therefore, the application can realize testing of battery negative electrode material magnetic substances by using scientific, economical, and simple-to-operate laboratory conventional devices, and is very suitable for sample pretreatment when testing magnetic substances by using an inductively coupled plasma optical emission spectrometer (ICP-OES) or an inductively coupled plasma mass spectrometer (ICP-MS), thus greatly improving testing accuracy. Furthermore, the application can be expanded to test particle size, morphology, and quantity distribution of magnetic substances by using SEM-EDS, thus providing certain ideas and technical support for testing of magnetic substances. BRIEF DESCRIPTION OF DRAWINGS

[0015] The accompanying drawings are included to provide a further understanding of the application and are incorporated in and constitute a part of this specification, illustrate exemplary embodiments of the application and explain the principles of the application, but do not limit the application.

[0016] Figure 1 It is a flow chart of a testing method of a magnetic substance of a battery negative electrode material. Figure 2 It is a structural schematic diagram of a testing device of a magnetic substance of a battery negative electrode material.

[0017] Wherein, 1, rotating motor, 2, bottle plug, 3, cantilever, 4, negative electrode mixture, 5, detachable adsorption magnetic rod group, 6, ultrasonic device water bath part, 7, ultrasonic device control base, 8, power time control panel. DETAILED DESCRIPTION

[0018] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are some but not all of the embodiments of the present application. The components of the embodiments of the present application described and shown in the drawings herein can be arranged and designed in various different configurations.

[0019] Theories or mechanisms described and disclosed in the present application, whether correct or not, should not be used to limit the scope of the present application, that is, the content of the present application can be implemented without being limited by any particular theory or mechanism.

[0020] In the present application, all the features defined in the form of numerical range or percentage range such as numerical value, quantity, content and concentration are only for the sake of brevity and convenience. Therefore, the description of numerical range or percentage range should be considered to have covered and specifically disclosed all possible sub-ranges and individual numerical values (including integers and fractions) within the range.

[0021] In the present application, unless otherwise specified, “comprise”, “include”, “contain”, “have” or similar terms cover the meaning of “consist of” and “consist essentially of”, for example, “A comprises a” covers the meaning of “A comprises a and other” and “A only comprises a”.

[0022] In the present application, in order to make the description simple, all possible combinations of various technical features in each embodiment or example are not described. Therefore, as long as the combinations of technical features do not contradict each other, the technical features in each embodiment or example can be combined arbitrarily, and all possible combinations should be considered as the scope disclosed in the specification.

[0023] The application will be further described in connection with the following specific embodiments. It should be understood that these embodiments are only used to illustrate the application and not used to limit the scope of the application. Furthermore, it should be understood that after reading the content of the application, those skilled in the art can make various modifications or changes to the application, and these equivalent forms also fall within the scope defined by the appended claims.

[0024] The following examples use the conventional apparatus in the art. The experimental method in the following examples is not specified, and is usually carried out according to the conventional conditions or the conditions recommended by the manufacturer. Various raw materials are used in the following examples, and unless otherwise specified, the conventional commercially available products are used, and the specifications are the conventional specifications in the art. In the specification of the application and the following examples, unless otherwise specified, “%” means weight percent, “parts” means weight parts, and the ratio means weight ratio.

[0025] How to improve the current negative electrode material for lithium battery in the processing of testing magnetic substances, due to the large specific surface area of the material, porous material and other causes, the magnetic substances are difficult to be completely adsorbed when adsorbed by the conventional polytetrafluoroethylene coated magnetic rod, the accuracy of the final test value of the magnetic substance is improved, and accurate guidance is brought to industrial production, and the electrochemical performance and safety of the subsequent battery are improved.

[0026] The application provides a battery negative electrode material magnetic substance testing method, which comprises the following steps: S1, dispersing the battery negative electrode material in anhydrous ethanol to form a mixed solution; S2, ultrasonic pretreatment is performed on the mixed solution, so that the magnetic substance is detached from the battery negative electrode material, and an ultrasonic treated mixed solution is formed; S3, in the ultrasonic treated mixed solution, the magnetic substance detached from the battery negative electrode material is adsorbed by the polytetrafluoroethylene coated magnetic rod; S4, after the adsorption is completed, the polytetrafluoroethylene coated magnetic rod adsorbed with the magnetic substance is washed, and after acid digestion treatment, a digestion solution is obtained; S5, based on the digestion solution, the content of the magnetic substance is tested by an inductively coupled plasma instrument, and the battery negative electrode material magnetic substance testing is completed.

[0027] The battery negative electrode material magnetic substance testing method of the present application is aimed at the current battery negative electrode material which is mostly graphite or silicon-based material, is a porous material, and has a relatively large specific surface area, so that the magnetic substance is gathered and adsorbed in the pores or on the surface. The existing conventional method is to use a magnetic rod coated with polytetrafluoroethylene to roll and adsorb, and to shake and adsorb. It is difficult to adsorb the magnetic substance firmly adsorbed in the pores onto the magnetic rod coated with polytetrafluoroethylene. Therefore, the present application uses a powerful ultrasonic means to loosen the magnetic substance gathered and adsorbed in the porous material, and to desorb and disperse in the solution. The magnetic substance is completely adsorbed on the magnetic rod coated with polytetrafluoroethylene as much as possible, and then is digested and tested. Thus, the problem of incomplete adsorption caused by the retention of the magnetic substance in the pores due to the porosity of the negative electrode material can be improved. The desorbed magnetic substance is captured in time. After acid digestion, the test is performed, and the accuracy and reliability of the test data are improved.

[0028] As shown in Figure 1 In some embodiments, the specific processing steps of the battery negative electrode material magnetic substance testing method of the present application are as follows: Step 1: 50~200g of negative electrode material is taken according to the national standard method and is added to a sample tank; Step 2: 300~500mL of anhydrous ethanol is added, the sample tank is tightly closed, and is shaken uniformly to disperse the negative electrode sample uniformly in the anhydrous ethanol; Step 3: The ultrasonic power is set to 100W~500W and the ultrasonic time is set on a conventional ultrasonic cleaning machine. The ultrasonic device is started to pretreat the negative electrode material for 0.5 hours. The magnetic substance is desorbed by manually inverting and mixing three times during the treatment; Step 4: After the ultrasonic treatment, a magnetic rod coated with polytetrafluoroethylene (6000GS~14000GS) is added to roll and adsorb at 80~160r / min for 30min; Step 5: After the adsorption, the magnetic rod coated with polytetrafluoroethylene is retained, and the anhydrous ethanol and negative electrode material solution are discharged together. The magnetic rod coated with polytetrafluoroethylene is cleaned (100ml of pure water is added, mixed for one minute, and then ultrasonic treatment is performed for one minute. The cleaning solution is then poured out) to remove the residual negative electrode material (100ml of pure water is used to clean twice to remove the negative electrode material, and 50mL of ethanol is used to clean three times); Step 6: 6mL aqua regia is added, and the polytetrafluoroethylene-coated magnetic bar is completely immersed in pure water, placed on a heating device, heated and ensured to be micro-boiled for 30min to digest the magnetic material adsorbed on the polytetrafluoroethylene-coated magnetic bar, and during the heating process, attention should be paid to whether the polytetrafluoroethylene-coated magnetic bar is completely immersed, and if not, pure water should be added. After heating is completed, it is taken out and naturally cooled to room temperature. The cooled solution is moved to a 100ml capacity bottle, and the digestion container and the polytetrafluoroethylene-coated magnetic bar are washed with a small amount of pure water for 3-4 times, and the washing liquid is combined into the capacity bottle, and the volume is fixed, shaken, and the subsequent steps are tested. The digestion temperature is controlled at 120℃-180℃. According to the different heat transfer efficiencies of each heating device, the aqua regia is adjusted to be in a micro-boiling state to ensure that the magnetic material is completely digested.

[0029] As shown in Figure 2 The battery negative material magnetic substance testing equipment of the application, the testing equipment is used to execute the battery negative material magnetic substance testing method, the testing equipment includes an ultrasonic device water bath part 6 (such as a sample jar) and an ultrasonic device control base 7 arranged from top to bottom, the ultrasonic device water bath part 6 contains a negative electrode mixed solution 4 (such as dispersing the battery negative material in anhydrous ethanol to form a mixed solution), the negative electrode mixed solution 4 is provided with a detachable adsorption magnetic bar group 5 (such as a polytetrafluoroethylene-coated magnetic bar), the detachable adsorption magnetic bar group 5 is connected to one end of a cantilever 3, the other end of the cantilever 3 extends out of the ultrasonic device water bath part 6 and is connected to a rotary motor (1), the ultrasonic device water bath part 6 has an opening, the opening position has a bottle plug 2, and the cantilever 3 penetrates through the bottle plug 2; the ultrasonic device control base 7 is provided with a power time control panel 8. The ultrasonic power and time can be set by controlling the power time control panel 8, and the battery negative material magnetic substance testing can be realized in combination with the sample jar (ultrasonic device water bath part 6), anhydrous ethanol (negative electrode mixed solution 4) and the detachable adsorption magnetic bar group 5 (such as a polytetrafluoroethylene-coated magnetic bar).

[0030] The battery negative material magnetic substance testing method of the application will be further described in detail through specific embodiments.

[0031] Example 1; Reference GB / T 33827-2017 "lithium ion nanometer negative material in the test method of magnetic material", take 50.332g negative material into the sample tank, add 400ml of anhydrous ethanol, tighten the sample tank, shake evenly, make the negative sample evenly dispersed in anhydrous ethanol, then set the ultrasonic power to 500w / 40khz on the conventional ultrasonic cleaning machine, open the ultrasonic device to pretreat the negative material for 0.3h, so that the magnetic material is detached, after ultrasonic, add the magnetic bar coated with polytetrafluoroethylene (the magnetic field intensity of the magnetic bar coated with polytetrafluoroethylene is controlled to 6000gs) cleaned in advance on the magnetic stirrer to roll and adsorb for 10min, after adsorption, clean the magnetic bar coated with polytetrafluoroethylene to remove residual negative material (clean with water twice to remove negative material, and clean with 50ml of ethanol three times respectively), put the magnetic bar into the container, add 6ml of aqua regia and pure water to immerse the magnetic bar coated with polytetrafluoroethylene, heat the magnetic material adsorbed on the magnetic bar coated with polytetrafluoroethylene to micro boiling digestion, and constant volume to 100ml, the results are as follows:

[0032] Example 2; Reference GB / T 33827-2017 "lithium ion nanometer negative material in the test method of magnetic material", take 49.938g negative material into the sample tank, add 400ml of anhydrous ethanol, tighten the sample tank, shake evenly, make the negative sample evenly dispersed in anhydrous ethanol, then set the ultrasonic power (500w / 40khz) on the conventional ultrasonic cleaning machine, open the ultrasonic device to pretreat the negative material for 0.5h, so that the magnetic material is detached, after ultrasonic, add the magnetic bar coated with polytetrafluoroethylene (the magnetic field intensity of the magnetic bar coated with polytetrafluoroethylene is controlled to 6000gs) cleaned in advance on the roller to roll and adsorb for 30min, after adsorption, clean the magnetic bar coated with polytetrafluoroethylene to remove residual negative material (clean with water twice to remove negative material, and clean with 50ml of ethanol three times respectively), put the magnetic bar into the container, add 6ml of aqua regia and pure water to immerse the magnetic bar coated with polytetrafluoroethylene, heat the magnetic material adsorbed on the magnetic bar coated with polytetrafluoroethylene to micro boiling digestion, and constant volume to 100ml, the results are as follows:

[0033] Example 3; Reference GB / T 33827-2017 "lithium ion nanometer negative material in the test method of magnetic material", take 50.050g negative material into the sample tank, add 400ml of anhydrous ethanol, tighten the sample tank, shake evenly, make the negative sample evenly dispersed in anhydrous ethanol, then set the ultrasonic power (500w / 40khz) on the conventional ultrasonic cleaning machine, open the ultrasonic device to pretreat the negative material for 1.0h, so that the magnetic material is detached, after ultrasonic, add the coated with polytetrafluoroethylene magnetic bar (the magnetic field intensity of the coated with polytetrafluoroethylene magnetic bar is controlled to 6000gs) in the magnetic stirrer to roll and adsorb for 30min, after adsorption, clean the coated with polytetrafluoroethylene magnetic bar to remove residual negative material (clean with water twice to remove negative material, and clean with 50ml of ethanol three times respectively), put the magnetic bar into the container, add 6ml of aqua regia and pure water to immerse the coated with polytetrafluoroethylene magnetic bar, heat the magnetic material adsorbed on the coated with polytetrafluoroethylene magnetic bar to micro boiling digestion, and constant volume to 100ml, the results are as follows:

[0034] Example 4; Reference GB / T 33827-2017 "lithium ion nanometer negative material in the test method of magnetic material", take 50.050g negative material into the sample tank, add 400ml of anhydrous ethanol, tighten the sample tank, shake evenly, make the negative sample evenly dispersed in anhydrous ethanol, then set the ultrasonic power (100w / 40khz) on the conventional ultrasonic cleaning machine, open the ultrasonic device to pretreat the negative material for 1.0h, so that the magnetic material is detached, after ultrasonic, add the coated with polytetrafluoroethylene magnetic bar (the magnetic field intensity of the coated with polytetrafluoroethylene magnetic bar is controlled to 14000gs) in the magnetic stirrer to roll and adsorb for 30min, after adsorption, clean the coated with polytetrafluoroethylene magnetic bar to remove residual negative material (clean with water twice to remove negative material, and clean with 50ml of ethanol three times respectively), put the magnetic bar into the container, add 6ml of aqua regia and pure water to immerse the coated with polytetrafluoroethylene magnetic bar, heat the magnetic material adsorbed on the coated with polytetrafluoroethylene magnetic bar to micro boiling digestion, and constant volume to 100ml, carry out the subsequent test of magnetic material of battery negative material, the results are as follows:

[0035] Example 5; Referring to GB / T 33827-2017《Test method of magnetic substances in nano negative electrode material for lithium ion》, 50.050 g of negative electrode material was added to a sample tank, 400 mL of anhydrous ethanol was added, the sample tank was tightly closed, and the negative electrode sample was uniformly dispersed in the anhydrous ethanol by shaking, and then the ultrasonic power (300 W / 40 KHz) was set on the conventional ultrasonic cleaning machine, and the ultrasonic device was started to pretreat the negative electrode material for 1.0 h to make the magnetic substances detached, after the ultrasonic treatment, a magnetic bar coated with polytetrafluoroethylene (the magnetic field strength of the magnetic bar coated with polytetrafluoroethylene was controlled to be 10000 GS) was added to the magnetic stirrer and rolled for 30 min to adsorb, after the adsorption was completed, the magnetic bar coated with polytetrafluoroethylene was cleaned to remove the residual negative electrode material (cleaned twice with water to remove the negative electrode material, and cleaned three times with 50 mL of ethanol), the magnetic bar was placed in a container, 6 mL of aqua regia and pure water were added to immerse the magnetic bar coated with polytetrafluoroethylene, the magnetic substances adsorbed on the magnetic bar coated with polytetrafluoroethylene were heated and slightly boiled for digestion, and the volume was made to 100 mL, and the subsequent test of the magnetic substances in the battery negative electrode material was carried out, and the results were as follows:

[0036] The following specific comparative examples are used as comparative methods of the embodiment of the test method of the magnetic substances in the battery negative electrode material.

[0037] Comparative Example 1 Referring to GB / T 33827-2017《Test method of magnetic substances in nano negative electrode material for lithium ion》, 50.050 g of negative electrode material was added to a sample tank, 400 mL of anhydrous ethanol was added, the sample tank was tightly closed, and the negative electrode sample was uniformly dispersed in the anhydrous ethanol by shaking, and then the ultrasonic power (300 W / 40 KHz) was set on the conventional ultrasonic cleaning machine, and the ultrasonic device was started to pretreat the negative electrode material for 1.0 h to make the magnetic substances detached, after the ultrasonic treatment, a magnetic bar coated with polytetrafluoroethylene (the magnetic field strength of the magnetic bar coated with polytetrafluoroethylene was controlled to be 10000 GS) was added to the magnetic stirrer and rolled for 30 min to adsorb, after the adsorption was completed, the magnetic bar coated with polytetrafluoroethylene was cleaned to remove the residual negative electrode material (cleaned twice with water to remove the negative electrode material, and cleaned three times with 50 mL of ethanol), the magnetic bar was placed in a container, 6 mL of aqua regia and pure water were added to immerse the magnetic bar coated with polytetrafluoroethylene, the magnetic substances adsorbed on the magnetic bar coated with polytetrafluoroethylene were heated and slightly boiled for digestion, and the volume was made to 100 mL, and the subsequent test of the magnetic substances in the battery negative electrode material was carried out, and the results were as follows:

[0038] Comparative Example 2 Referring to GB / T 33827-2017 "Test Method for Magnetic Materials in Nanoscale Anode Materials for Lithium-ion Applications", 51.285 g of the anode sample was weighed and added to a clean sample container. 300 mL of anhydrous ethanol was added, followed by a clean PTFE-coated magnetic rod (6000GS). The container was tightly sealed and thoroughly shaken. The sample container was then placed on a rolling device at a speed of 60 r / min for 30 min of rolling adsorption. The container was shaken every 10 min during rolling, for a total of 3 times. After rolling, the PTFE-coated magnetic rod was removed and placed in an Erlenmeyer flask. After rinsing with water, 50 mL of anhydrous ethanol was added, and the mixture was ultrasonically cleaned for 1 min, repeated three times. The PTFE-coated magnetic rod and the Erlenmeyer flask were then rinsed with water three times. 4.5 mL of aqua regia was added, followed by pure water to submerge the magnetic rod. The mixture was heated to a gentle boil for 30 min to dissolve the aqua regia. The volume was then adjusted to 100 mL. The results are as follows:

[0039] As can be seen from the comparison above, the test results are extremely unstable, especially for Ni, and the test values ​​are significantly smaller.

[0040] As can be seen from the comparison between the examples and the comparative examples, the magnetic material content of the negative electrode material in the examples after ultrasonic pretreatment is almost three times that of the comparative examples without ultrasonic treatment. Moreover, the stability is also greatly improved when ultrasonic treatment lasts for more than 0.5 hours, which greatly improves the accuracy of the data results.

[0041] In addition, the effects of two pretreatment methods on the negative electrode material were compared. The particle size test results showed that ultrasound made the particle size of the negative electrode material smaller, eliminated the agglomeration phenomenon inside the material, and greatly increased the content of the final magnetic material, which can better reflect the true value.

[0042]

[0043] In summary, this invention provides a testing method and apparatus for magnetic materials in battery anode materials. By utilizing powerful ultrasonic assistance, it solves the problem of incomplete adsorption during the adsorption of magnetic materials in battery anode materials onto polytetrafluoroethylene-coated magnetic rods, resulting in lower test values. It offers a relatively economical, rapid, and easy-to-operate testing method that can be implemented using conventional laboratory equipment. This invention is applicable to the pretreatment adsorption steps of battery anode materials in conventional laboratory inductively coupled plasma optical emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS) testing, improving the accuracy and reliability of the results. Furthermore, it reduces the skill requirements for operators, simplifies the experiment, and provides technical support for accurate testing of magnetic materials in the laboratory, battery manufacturing process control, and environmental assessment, demonstrating excellent practicality.

[0044] Finally, it needs to be explained that the above is only the preferred embodiment of the present application, and does not limit the present application in any form; anyone skilled in the art can easily implement the present application according to the description and the above, and make some changes, modifications and equivalent changes of the above disclosed technical content, which are equivalent embodiments of the present application; at the same time, any equivalent changes, modifications and evolution of the above embodiments according to the essential technology of the present application are still within the protection scope of the technical solutions of the present application.

Claims

1. A method for testing the magnetic material of a battery negative electrode, characterized in that, Includes the following steps: S1. Disperse the battery negative electrode material in anhydrous ethanol to form a mixture; S2. The mixture is pretreated by ultrasound to desorb the magnetic material from the negative electrode material of the battery, forming a mixture after ultrasound treatment. S3. In the mixture after ultrasonic pretreatment, magnetic materials desorbed from the negative electrode material of the battery are adsorbed by a magnetic rod coated with polytetrafluoroethylene. S4. After adsorption, clean the polytetrafluoroethylene-coated magnetic rod that has adsorbed magnetic materials, and then obtain the digestion solution by acid digestion. S5. Based on the digestion solution, the content of magnetic materials is tested using an inductively coupled plasma instrument to complete the testing of magnetic materials in the battery negative electrode material.

2. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In S1, the mass ratio of the added lithium battery negative electrode material to anhydrous ethanol in the mixture is controlled to be 2:3~20.

3. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In S2, the parameters in the ultrasonic pretreatment are controlled as follows: The ultrasonic power is controlled at 100W~500W, and the ultrasonic time is controlled at 0.3h~1h; the ultrasonic treatment is paused and mixed at least three times.

4. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In step S3, the adsorption of the magnetic rod coated with polytetrafluoroethylene is achieved by rolling adsorption or stirring adsorption.

5. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In step S3, the magnetic field strength of the PTFE-coated magnetic rod is 6000GS~14000GS, and the adsorption time of the PTFE-coated magnetic rod is controlled to be 10min~60min.

6. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In step S4, the operation of cleaning the polytetrafluoroethylene-coated magnetic rod that has adsorbed magnetic material includes: first cleaning with pure water to remove residual negative electrode material, and then cleaning with ethanol.

7. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In S4, aqua regia is used as the digestion reagent in the acid digestion process. The magnetic rod coated with polytetrafluoroethylene and adsorbed with magnetic material is placed into a container filled with aqua regia for acid digestion. The dosage of aqua regia is controlled as follows: the mass ratio of aqua regia to the negative electrode material of the battery is 3:25-3:100; and after adding aqua regia to the container, water is added as needed until the liquid in the container submerges the PTFE-coated magnetic rod that has adsorbed magnetic materials.

8. The method for testing magnetic materials in battery negative electrode materials according to claim 7, characterized in that, In S4, during the acid digestion process: the acid digestion temperature is controlled at 120℃~180℃, and the acid digestion time is controlled at 20min-40min.

9. The method for testing magnetic materials in battery negative electrode materials according to claim 1, characterized in that, In S5, the inductively coupled plasma instrument is an inductively coupled plasma emission spectrometer or an inductively coupled plasma mass spectrometer.

10. A testing device for magnetic materials used in battery negative electrode materials, characterized in that, The testing equipment is used to perform the test method for the magnetic material of the battery negative electrode material according to any one of claims 1-9. The testing equipment includes an ultrasonic device water bath part (6) and an ultrasonic device control base (7) arranged from top to bottom. The ultrasonic device water bath part (6) contains a negative electrode mixture (4). A detachable magnetic rod group (5) is placed in the negative electrode mixture (4). The detachable magnetic rod group (5) is connected to one end of a cantilever (3). The other end of the cantilever (3) extends out of the ultrasonic device water bath part (6) and is connected to a rotary motor (1). The ultrasonic device control base (7) is provided with a power and time control panel (8).